2020
DOI: 10.3390/plants9030377
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Cellular Functions of the Microdomain-Associated FWL/CNR Protein Family in Plants

Abstract: Membrane microdomains/nanodomains are sub-compartments of the plasma membrane enriched in sphingolipids and characterized by their unique protein composition. They play important roles in regulating plant development and plant-microbe interactions including mutualistic symbiotic interactions. Several protein families are associated with the microdomain fraction of biological membranes such as flotillins, prohibitins, and remorins. More recently, GmFWL1, a FWL/CNR protein exclusively expressed in the soybean no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Recent studies have established that the GmFWL1 protein is located in plasma membrane microdomains [27,28], shedding light on the molecular function of plant FWL proteins. Membrane microdomains are sub-compartments of biological membranes and comprise special lipids and proteins [23,45]. They play important roles in diverse biological processes, such as membrane transport and signal transduction [45,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have established that the GmFWL1 protein is located in plasma membrane microdomains [27,28], shedding light on the molecular function of plant FWL proteins. Membrane microdomains are sub-compartments of biological membranes and comprise special lipids and proteins [23,45]. They play important roles in diverse biological processes, such as membrane transport and signal transduction [45,53].…”
Section: Discussionmentioning
confidence: 99%
“…The FW2.2 protein harbors an uncharacterized placenta-specific 8 domain, and is localized to the plasma membrane [21,22]. FW2.2-like (FWL) genes have been characterized in various plant species and reported to perform diverse functions [23][24][25]. Cell Number Regulator1 (CNR1), an FWL gene in maize, negatively regulates plant and organ size by controlling cell division [22].…”
Section: Introductionmentioning
confidence: 99%
“…The PLAC8 motif is present in hundreds of proteins in plants, animals and fungi, ranging in size from 108 to 557 amino acids (Guo et al, 2010;Song et al, 2011). In a recent survey, Thibivilliers et al (2020) restricted the plant CNR/FWL family to 134 members across 13 different species belonging to various phyla of the plant kingdom. The PLAC8 domain is composed of one or two hydrophobic segments, predicted to form transmembrane (TM) helices (Song et al, 2004).…”
Section: Fw22 and Cnr/fwl Are Transmembrane Proteins Containing A Pla...mentioning
confidence: 99%
“…As identified by Thibivilliers et al (2020), the CNR/FWL family in tomato is made up of twelve members, including FW2.2. Unfortunately, there is no functional analysis yet available for FW2.2 and the SlFWLs.…”
Section: Fw22 and Its Homologs Play A Part In Plant Organogenesis And...mentioning
confidence: 99%
“…Moreover, it was found that the kelch-repeat domain of IbFBK interacts with IbCNR8 (CELL NUMBER REGULATOR 8), which was suggested to lead to the ubiquitination and degradation of IbCNR8. CNRs are transmembrane proteins known as the regulators of plant organ size (see [174]). In soybean, the member of the CNR protein family, GmFWL1, has been identified, which exclusively is expressed in the root hair cells in response to rhizobia and in the nodules.…”
Section: Players Of Systemic Response To Nutrient Availability and Their Role In Nodulationmentioning
confidence: 99%